Ekosistem Fintech Syariah: Meninjau Model Pinjaman Online dalam Bingkai Ekonomi Islam - Merly Cahya Putri (Jurnal Multidisiplin Indonesia, 2024)
This study aims to analyze the Islamic fintech ecosystem in Indonesia, focusing on online lending models that comply with Islamic economic principles. Islamic fintech offers inclusive and fair financing solutions, particularly for micro and small enterprises (MSEs). The research method used is qualitative descriptive, with data collection through in-depth interviews, document studies, and observations. Data obtained from industry players and users of online lending services show that, although Islamic fintech has great potential to expand financial inclusion, the main challenges include low financial literacy in Islamic finance and limitations in regulatory oversight. The findings imply the need for increased education on Islamic economic principles and strengthened regulations to ensure the healthy and sustainable development of Islamic fintech. This study is expected to contribute to the development of Islamic fintech as an alternative financing model that is more inclusive and based on Islamic principles.